A failed marriage between standardization and incentivism: Divergent perspectives on the aims of performance-based compensation in Shanghai, China - Priya Goel La Londe (Arizona State University, 2017)
The Chinese province of Shanghai has gained international recognition as a high performing education system with strong teaching and learning outcomes. One accountability mechanism in Shanghai's education reform strategy is statewide performance-based compensation (PBC), also known as performance- or merit pay. Providing a first time account of PBC in the Shanghai context, this study investigated variance in stated and perceived aims of this policy instrument. To explore this variance, the study drew on data from national, state, and school level policy documents, and data from interviews with 20 teachers and the principal in a high performing elementary school. The analysis revealed that PBC was intended to improve teaching quality. However, the teachers' perceived merit pay was meant to increase teacher enthusiasm, job satisfaction, and participation in teacher and student development activities. Importantly, the teachers perceived these aims as tangential from instructional improvement goals. Based on these findings, I argue that this particular PBC policy, as a manifestation of the marriage of standardization and incentivism, is unable to fulfill the promises of this marriage - to link incentives with homogenous, uniform metrics associated with a generic and shared notion of teaching quality.